تقييم مرض ابيضاض الدم اللمفاوي المزمن التظاهرات السريرية ، الموجودات المخبرية ، المضاعفات والمعالجة خبرة مشفى الأسد الجامعي في اللاذقية - جرجس ميخائيل; جالق رياض; فران فاطمة (Latakia University Journal -Medical Sciences Series, 2019)
شملت هذه الدراسة الإحصائية (30) مريضاً مصاباً بابيضاض الدم اللمفاوي المزمن راجعوا مشفى الأسد الجامعي في اللاذقية بين عامي 1999-2002. كانت نتائج البحث كالتالي : (76%) من المرضى كانوا من الذكور ، نسبة إصابة الذكور إلى الإناث 3,3: 1،(83%) من المرضى كانوا بأعمار فوق (50 سنة) ، وتراوحت الأعمار ما بين (38-75) سنة حيث بلغ العمر الوسطي للمرضى عند وضع التشخيص (62,9) سنة . لقد كانت ضخامة العقد اللمفاوية السطحية وضخامة الطحال والكبد أكثر الموجودات السريرية شيوعياً عند وضع التشخيص حيث وجدت بالنسب التالية: 53% ، 40% ، 26% ، على الترتيب. كانت أهم الموجودات المخبرية ثبوتاً وفي كل المرضى كثرة اللمفاويات في الدم المحيطي وفي نقي العظم 66% من المرضى كان لديهم ارتشاح نقي العظم باللمفاويات بنسبة تفوق 50% عند وضع التشخيص . اعتبر تعداد اللمفاويات المطلق في الدم > 10000 / مم3 مع وجود نسبة لمفاويات في نقي العظم ، 30% كافياً لإثبات التشخيص. وفي حال كان تعداد اللمفاويات المطلق في الدم < 10000 / مم3 وجب عندها إجراء التنميط المناعي لتأكيد التشخيص. تم إجراء التنميط المناعي للمفاويات الجائلة في الدم لـ (12) مريضاً ، كانت أكثر الواسمات إيجابية (CD45) ، (CD19) ،( CD23) ،( CD20) ، (CD5) ،( CD22 )، وبالنسب التالية وعلى الترتيب: (91%) ، (91%) ،( 66%) ،( 58%) ، (50%) ، (25%) . مثّلت الأخماج أهم المضاعفات شيوعاً (خاصة ذوات الرئة) ووجدت بنسبة 16% . صنف المرضى في ثلاث مجموعات علاجية: المجموعة الأولى: مراقبة وانتظار وضمت 4 مرضى. المجموعة الثانية: المعالجة التقليدية وضمت 23 مريضاً ، المجموعة الثالثة: المعالجة الحديثة وضمت 3 مرضى. This statistical study included (30) patients with CLL, who had been admitted at Al-Assad University hospital in Lattakia between 1999-2002, The results of this research were: - (76) percent of the patients were males, male to female ratio was 3.3: 1, (83) percent of the patients were over (50) years old, the range of ages was from 38 to75 years with a median age at diagnosis of (62,9) years. - The most commonly abnormal Findings on physical examination at the time of initial diagnosis were lymphadenopathy, splenomegaly and hepatomegaly presented in 53%,40%, 26%, of patients respectively. - The most evident abnormalities among laboratory findings were lymphocytosis in the blood and the bone marrow, presented in all patients, (66) percent of the patients had infiltrative bone marrow with lymphocytes accounting for more (50) percent of all nucleated cells at the time of initial diagnosis. - Absolute lymphocyte count in the peripheral blood > 10,000/mm3 and bone marrow lymphocytes accounting for > 30 percent were enough for diagnosis in patients with an absolute lymphocy te count < 10,000/mm3, lymphocyte phenotyping was required. - Phenotype of circulating lymphocytes was performed in (12) patients, the most positive markers were: (CD45,CD19,CD23,CD20,CD5,CD22) presented in (91%, 91%, 66%, 58%, 50%, 25%,) of patients respectively. - The most common complication was infection (specially pneumonia) presented in (16) percent of patients. - Patients were classified in three groups for therapy: first group: watch and wait. It included (4) patients Second group: traditional therapy. it included (23) patients. Third group: new agents. it included (3) patients.